The alteration from agricultural to nomadic regimes resulted in human livelihood transformation in North-Central China during the 12th century: The archaeobotanical evidence - Li, Ruo; Li, Bing; Chen, Wei; Liu, Peilun; Xie, Mingxia; Zhang, Yunqing; Wang, Sai; Li, Yuecong; Dong, Guanghui (Frontiers in Plant Science, 2022)
Human livelihoods provided a crucial economic foundation for social development in ancient times and were influenced by various factors including environmental change, agricultural origin and intensification, as well as long-distance exchange and culinary tradition. The effect of geopolitical change on human subsistence, especially the shifts between agricultural and nomadic regimes, has not been well understood due to the absence of detailed historical records and archaeological evidence. During the 12th century, the control of the Zhengding area in Hebei Province of north-central China changed from the Northern Song (960–1127 CE) to the Jurchen Jin Dynasty (Jin Dynasty; 1115–1234 CE). Recent excavation of the Zhengding Kaiyuan Temple South (ZKS) site in the area provides a rare opportunity to study human livelihood transformation in relation to geopolitical change. In total, 21,588 charred crop caryopses including foxtail millet, wheat, broomcorn millet, hulled barley, and rice, and other carbonized remains including 55.15 g of boiled foxtail millet and 353.5 g of foxtail millet caryopses were identified, and nine AMS 14C dates of crop remains were obtained from the Northern Song and Jin layers at the ZKS site. This revealed that the dominant plant subsistence transformed from wheat to foxtail millet during the change from the Northern Song to the Jin Dynasties in Zhengding area. By comparing with historical documents and paleoclimate records, we propose that this abnormal shift of primary staple food from the relatively high-yield wheat to low-yield foxtail millet was induced by the traditional dietary preference for foxtail millet in the nomadic Jin society. The Jin government levied foxtail millet as taxation and promoted massive immigration from northeastern China to north-central China to consolidate their rule, which resulted in the adoption of foxtail millet as the most important crop in Zhengding area. The advantage for the cultivation of this frost-sensitive crop in north-central China over northeast China was probably enhanced by notable cold events during the 12th century, while the primary influencing factor for the transformation of human livelihoods in north-central China during that period was geopolitics rather than climate change.